Protocol to screen for Sorafenib resistance regulators using pooled lentiviral shRNA library and a Sorafenib-resistant hepatocellular carcinoma cell model - Gao, Ruize; Tang, Fengyuan; Christofori, Gerhard (STAR protocols, 2023)
Approaches to study therapy resistance in HCC (hepatocellular carcinoma) are limited, especially when using HCC models in vitro. Here, we present a protocol to establish an in vitro Sorafenib-resistant human HCC cell model and conduct an shRNA-mediated synthetic lethal screen in established Sorafenib-resistant HCC cell lines to identify critical regulators of Sorafenib resistance. We describe steps for RNA sequencing and functional analysis to reveal the mode of action of potential candidates in conferring therapy resistance to HCC cells. For complete details on the use and execution of this protocol, please refer to Gao et al. (2021a)1 and Gao et al. (2021b).2 [Display omitted] •Establishment of in vitro Sorafenib-resistant HCC cell models•Establishment of intrinsic or acquired drug-resistant cancer cell lines•Global transcriptomic analysis by RNA sequencing•Synthetic lethal screen using genome-wide pooled lentiviral shRNA libraries Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics. Approaches to study therapy resistance in HCC (hepatocellular carcinoma) are limited, especially when using HCC models in vitro. Here, we present a protocol to establish an in vitro Sorafenib-resistant human HCC cell model and conduct an shRNA-mediated synthetic lethal screen in established Sorafenib-resistant HCC cell lines to identify critical regulators of Sorafenib resistance. We describe steps for RNA sequencing and functional analysis to reveal the mode of action of potential candidates in conferring therapy resistance to HCC cells.